The Novel Use of Saraca thaipingensis Leaf Powder as Potential Biosorbent Material for the Removal of Chromium(VI) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
Saraca thaipingensis or ‘Gapis’ tree, classified under the Fabaceae family is a native of Taiping; copious over Peninsular Malaysia and Southeast Asia. The withered and fallen dead leaves were collected from INTI International University’s garden walkway. To date, literature has yet to capture the use of S. thaipingensis tree parts or refuse as potential biosorbent material for the removal of heavy metals thus verifying the novelty of this study. Batch experiments were carried out with the leaf powder to study the effects of dosage, particle size and contact time towards Cr(VI) removal (%) at 1-100 mg/L. Results showed that Cr(VI) removal increased from 52.22% to 99.31% (p < 0.05) with increase in biosorbent dosage (0.005, 0.010, 0.015, 0.020, 0.025 and 0.050 g). The different particle size ranges tested were: 107-125, 126-150, 151-250, 251-500, and 501- 1000 ?m. Highest Cr(VI) removal of 99.53% was obtained with the 151-250 ?m particle size; further size decrease did not yield more removal (p > 0.05). The optimal Cr(VI) removal was recorded after 45 min (99.62%) and 90 min (99.76%) contact time (p > 0.05). Further characterization and optimization studies are being carried out to develop a novel, sustainable, low cost yet effective leaf powder based biosorbent material.
Keywords: Saraca thaipingensis; Biosorbent; Leaf powder; Cr(VI) removal; Cr(VI) uptake